Oculist's contributions to cataract operation - Asih, Devi Ratna; Ismail, Ahmad Faris (IIUM Press, 2011)
Numerous cultures including western civilization have added up knowlcdge accumulation to the r.ciences evolution. Unfonunatcly, Westerners have Jong been credited wilh discoveries made many centuries before them. ThUs. many of tile basic sciences ,",'cre invented by oon,Europeans, For instance, Modem Western medicine did nOI originate from Europe and that it actually arose from the Islamic orient (Ajram, 1992), Based on this point of view tbe objective of this chaptcr is 10 explore thc information of Islamic medical heritage. The methodology that applies for this chapter is dala compilation from library research and another variOIlS academic sources. The significance oflhis chapter can be seen in catamet uperation procedure are which is still recognized and use by our modern medical procedures practices